"Better Gestures": A Disability History Perspective on the Transition from (Silent) Movies to Talkies in the United States. Issue 1 (27th July 2016) - Johnson, Russell L.
Abstract: This essay focuses on two cultural shifts at the end of the 1920s, the watershed decade in the emergence of modern culture in the United States. First, in deaf education, oralism (lip-reading and audible speech) reached its peak level of control as the method of instruction, replacing manualism (sign language). Second, at the cinema, talkies replaced silent movies. In each case—manualism to oralism and silents to talkies—the central change involved using audible spoken language in place of a purely visual form of communication. Contemporaries wrote about these two historical shifts using remarkably similar terms. The silent movies that were produced during the transition period (1927–1930) were even sometimes called "dumbies, " recalling a common slur regarding the deaf. Yet historians have not made the connection. Scholarship on the transition to talkies emphasizes technological, production, and business challenges presented by sound, especially dialogue, in the cinema. Likewise, historians of the Deaf cultural experience in the United States emphasize the fight to preserve sign language, and although a few have noted that the arrival of the talkies led to (further) cultural exclusion of the deaf, these scholars focus more on the misrepresentation of deafness in films and the limited opportunities for deaf actors in Hollywood. This article argues that the concurrence of these two independent and seemingly unrelated historical changes—oralism and talkies—was not a coincidence. Both changes reflected larger beliefs about normalcy, language, communication, deafness, intelligence, and ultimately humanity in the early-twentieth century.